PARADIGMA DAKWAH DALAM PERSPEKTIF ISLAM DAN FILSAFAT - Hasyim Syamhudi (JURNAL AT-TURAS, 2015)
Islamic preaching (dakwah)  is pious activity as inspreable part of Muslims life, not merely because of Islam as preaching religion, but also that religion is in fact embraced by the most people of the world, then the Islamic preaching as a kind of science is not rightly questionable. However, a fact that Islamic preaching is a kind of science is debatable yet among experts since the systematic form of Islamic preaching is not really different from the common communication with the communicator, communican, message, and channel. So it is also case for the Islamic preaching with da’i, mad’u, Islamic materials, and preaching media. Furthermore, this article attempts to set the Islamic preaching in the common sciences through an approach to philosophy of science in various perspectives, suchh as positivism, naturalism, phenomenology, and metaphysics, by integration between deductive and inductive theories. Before doing that, I attempt to do through the Islamic ways in the preaching because the Islamic preaching is not merely religious obligation, but also imprortantly a theoretical and praxical activity runnig on the basis of Islamic univeral mission, rahmatan lil al-‘âlamîn.